2016
DOI: 10.1016/j.celrep.2016.03.057
|View full text |Cite
|
Sign up to set email alerts
|

Neural Integration Underlying a Time-Compensated Sun Compass in the Migratory Monarch Butterfly

Abstract: Migrating Eastern North American monarch butterflies use a time-compensated sun compass to adjust their flight to the southwest direction. While the antennal genetic circadian clock and the azimuth of the sun are instrumental for proper function of the compass, it is unclear how these signals are represented on a neuronal level and how they are integrated to produce flight control. To address these questions, we constructed a receptive field model of the compound eye that encodes the solar azimuth. We then der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…Alternatively, the output of the entire circuit could be modulated according to time of day. While a recent study models how the Sun-compass may be time compensated (Shlizerman et al, 2016), it does not suggest a specific neural substrate and it remains to be shown whether the neural circuitry for representing current and desired headings is involved in azimuth compensation.…”
Section: Towards a General Concept Of Encoding Desired Headingsmentioning
confidence: 99%
“…Alternatively, the output of the entire circuit could be modulated according to time of day. While a recent study models how the Sun-compass may be time compensated (Shlizerman et al, 2016), it does not suggest a specific neural substrate and it remains to be shown whether the neural circuitry for representing current and desired headings is involved in azimuth compensation.…”
Section: Towards a General Concept Of Encoding Desired Headingsmentioning
confidence: 99%
“…noted, is a biologically tangible clock-to-compass circuit. Thus, a working mathematical model of the time-compensated sun compass has been proposed [51]. For this model, a receptive field of the compound eye that encodes solar azimuth was first constructed.…”
Section: Using a Time-compensated Sun Compassmentioning
confidence: 99%
“…The comparison of the sun sensors from Solar MEMS technologies are given in the following The field of view of these sensors is limited to ±60º which will not be able to cover the full spectrum for our application. To resolve this issue, five sensors can be used with the mounting shown in Figure 3 A majority of animal species including migrating Eastern North American monarch butterflies has the vision mediated by compound eyes [11] [16]. Floreano [16] have succeeded in fabricating a prototype of a miniature curved artificial compound eye named CurvACE which can calculate the solar azimuth based on photodetectors.…”
Section: Sensorsmentioning
confidence: 99%
“…The physical model they implemented uses the visual inputs from the structure based on Dorsal Rim Area (DRA) along with the temporal circadian rhythm and the polarization pathway where the combination of detected relative bearing from the sun and predicted sun azimuth is used to calculate absolute heading. [5] In the studies of migrating Eastern North American monarch butterflies performed by Shlizerman [11], they present a model that integrates neuronal oscillations of the sun's horizontal position and the circadian clock to direct flight and their model explains flight simulator tracks and proposes a space-time integration mechanism for directional flight. The monarchs use a circadian clock housed in the antennae which is capable of keeping track of time-of-day and to control the sun compass timings.…”
Section: Chapter Introductionmentioning
confidence: 99%
See 1 more Smart Citation